Advances in Chemistry and Biomedical Applications of Plasma Immersion Ion Implantation Treatments of Titanium Using Monte Carlo Simulations (Stop and Range Ions in Matter) - Sant'Ana, Péricles Lopes; Bortoleto, José Roberto R.; Cruz, Nilson Cristino da; Rangel, Elidiane Cipriano; Durrant, Steven F.; Santos, Nazir Monteiro dos (Current Advances in Chemistry and Biochemistry Vol. 7, 2021)
In this work it was analyzed the surface modification of a titanium alloy using plasma immersion ion implantation in order to improve its tribological properties such hardness and scratch resistance. Moreover, physical simulation using SRIM (stopping and range ions in matter) was used to examine the thickness of modified layers. From our PIII study of ti6al4v and titanium using nitrogen and hydrogen plasma when immersed in a methane atmosphere, nanoindentation and XPS investigations demonstrated an improved hardness and scratch resistance owing to the microstructures yielded, such as tin, TiO2 and DLC-Ti or tic.